PERENCANAAN STRATEGIS SISTEM INFORMASI BADAN KOORDINASI TAMAN KANAK AL QUR’AN DAN TAMAN PENDIDIKAN AL QUR’AN KABUPATEN BANTUL - Rosyid Hanif Fauzi; Mohammad Suyanto; Ferry Wahyu Wibowo (Informasi Interaktif, 2018)
The title of this research is The Stategic Planning of Information System in Badan Koordinasi Taman Kanak Al Qur’an dan Taman Pendidikan Al Qur’an Bantul Regency.  To manage TKA-TPA in Bantul Regency which consists of 909 units well, it needs to have strategic planning of Information system by using the development of IS/TI. This research is aimed to make a planning of strategic Information System by using framework Ward and Peppard to help the organization to achieve the vision, mission, and the goal of the organization.  This research is focused on the scope of strategic planning information system by using framework Ward and Peppard and Value Chain, SWOT and PEST method analysis. The research is started by analyzing the internal/external environment of organization and the information system recently based on framework Ward and Peppard by using certain analysis method. The next step is identify the needed of information system and give the proposal of the next information system based on the analysis result. The result of the research is the necessity of information system to manage TKA-TPA in Bantul Regency. Keyword: BADKO TKA-TPA, Ward and Peppard, Value Chain, SWOT , PEST